Impact of harm reduction care in HIV clinical settings on stigma and health outcomes for people with HIV who use drugs: study protocol for a mixed-methods, multisite, observational study. Issue 9 (16th September 2022) - Kay, Emma Sophia; Creasy, Stephanie; Batey, D Scott; Coulter, Robert; Egan, James E; Fisk, Stuart; Friedman, Mackey Reuel; Kinsky, Suzanne; Krier, Sarah; Noble, Victor; Turan, Bulent; Turan, Janet M; et al.
Abstract : Introduction: Our previous pilot work suggests relational harm reduction strengthens relationships between people with HIV (PWH) who use drugs and their healthcare providers and improves HIV health outcomes. However, there is limited research examining ways that structural (eg, strategies like syringe service programmes) and/or relational (patient-provider relationship) harm reduction approaches in HIV clinical settings can mitigate experiences of stigma, affect patient-provider relationships and improve outcomes for PWH who use drugs. Our mixed methods, multisite, observational study aims to fill this knowledge gap and develop an intervention to operationalise harm reduction care for PWH who use drugs in HIV clinical settings. Methods and analysis: Aim 1 will explore the relationship between healthcare providers' stigmatising attitudes towards working with PWH who use drugs and providers' acceptance and practice of structural and relational harm reduction through surveys (n=125) and interviews (n=20) with providers. Aim 2 will explore the interplay between patient-perceived harm reduction, intersectional stigma and clinical outcomes related to HIV, hepatitis C (if applicable) and substance use-related outcomes through surveys (n=500) and focus groups (k=6, total n=36) with PWH who use drugs. We will also psychometrically evaluate a 25-item scale we previously developed to assess relational harm reduction, the Patient Assessment of Provider Harm Reduction Scale. Aim 3 will use human-centred design approaches to develop and pretest an intervention to operationalise harm reduction care for PWH who use drugs in HIV clinical settings. Ethics and dissemination: This study was approved via expedited review by the University of Pittsburgh Institutional Review Board (STUDY21090002). Study findings will be presented in peer-reviewed journals and public health conferences as well as shared with patient participants, community advisory boards and harm reduction organisations. Trial registration number: NCT05404750 .